Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.
Upcoming SlideShare
Loading in …5
×

# Alg 1 day 53 ch. 6.2 continued

473 views

Published on

Published in: Education, Technology, Business
• Full Name
Comment goes here.

Are you sure you want to Yes No
Your message goes here
• Be the first to comment

• Be the first to like this

### Alg 1 day 53 ch. 6.2 continued

1. 1. Agenda Mon. 11/22 Do Now Homework Check More on Slope Intercept Form Homework 11 p. 294 # 38 - 55 41 - 49 write in Slope Intercept Form, then name slope & y-interc 50 - 55 put into Slope Intercept Form, then graph
2. 2. Determine whether these statement are true or false. Do Now Give justification for your answers. 1. All horizontal lines have the same slope. 2. A line with a slope of 1 always passes through the origin (0,0). 3. Two lines may have the same slope. 4. The slope of a line that passes through Quadrant III must have a negative slope. 5. A line with a slope of 0 never passes through point (0,0). 6. It is not possible to divide a number by zero. T F T T F F
3. 3. p. 294 # 4 - 15, 23 - 26, 28 - 32
4. 4. axes in red
5. 5. WRITING EQUATIONS IN SLOPE INTERCEPT FORMReview (0, -2) calculate slope 1 2 y-intercept -2 substitute for m and b y = x - 2 1 2
6. 6. Writing Equations in Slope-Intercept Form What is the slope and y-intercept of this line? 4y - 12 = 3x Needs to be put into slope-intercept form. Solve for y. 4y - 12 = 3x 4y = 3x + 12 + 12 + 12 Now divide each term by 4 4y = 3x + 12 4 4 4 y = 3x + 3 4
7. 7. Converting an equation to slope-intercept form
8. 8. WHITEBOARD PRACTICE Please put these equations into slope/intercept form, then give the slope and y-intercept. y = 3 - x m = -1 b = 3 2y = 4x + 8 m = 2 b = 4 6x + 3y = 4 m = -2 b = 4/3 y + 1/3x = -2 m = -1/3 b = -2 y/2 - 7x = 0 m = 14 b = 0 4x + y/4 = 5 m = -16 b = 20 6y - 2g = 4x m = 2/3 b = g/3 y = mx + b y = mx + b y = mx + by = mx + by = mx + b y = mx + b y = mx + b